Depresi Pada Penderita Cedera Kepala - Muhammad Abi Nubli (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2019)
Head injury (trauma capitis) is a mechanical injury that directly or indirectly affects the head resulting in injuries to the scalp, skull fracture, tearing of the lining of the brain and damage to the brain tissue itself, as well as resulting in neurological disorders. Psychiatric disorders, including mood, anxiety, and substance use disorders, are common after brain injuries, especially when injuries are moderate to severe, and interfere with health, social participation, and quality of life. Depression is the most common psychiatric condition after brain injury. Depression is a serious mental disorder characterized by feelings of sadness and anxiety. This disorder will usually disappear within a few days but can also be ongoing which can affect daily activities According to WHO, depression is a mental disorder characterized by the appearance of symptoms of decreased mood, loss of interest in something, feelings of guilt, sleep disturbance or appetite, loss of energy , and decreased concentration